Strategi Pengembangan Ekowisata Di Kawasan Budidaya Lebah Kele-Kele Di Desa Pejeng Kangin, Kabupaten Gianyar - Mochammad Azka Zahirul Sofyan; Ida Ayu Suryasih (JURNAL DESTINASI PARIWISATA, 2022)
The period of Covid-19 pandemic is one of the conditions that affects the motivation of tourists to travel in touristattractions that offer the beauty of nature, have minimal visitors and concerned about cleanliness and healthcare. Thepurpose of this study is to formulate the developing strategy of ecotourism in the kele-kele bee cultivation area, in PejengKangin Village, Gianyar Regency. The research approach uses a descriptive qualitative method and SWOT analysis.Data collection techniques used are observation and interviews. In this study primary data and secondary data used asdata sources. Primary data were obtained from observations in Pejeng Kangin Village and interviews with the head ofPOKDARWIS Pejeng Kangin Village and the head of the Sari Kele group. Secondary data were obtained from documentsthat can be reached from Pejeng Kangin Village. The results showed that the kele bee cultivation area of Pejeng KanginVillage was included in the type of forest ecotourism. The results of the SWOT analysis show that the strategy indeveloping ecotourism in kele-kele cultivation area, namely the promotion of ecotourism must be improved, in order toraise brand awareness to tourists who have an interest in nature and the manager must provide facilities andinfrastructure to support tourist attractions, such as adding boards directions to the kele-kele bee cultivation area.Keyword: Strategy Development, Ecotourism, Pokdarwis